Trade, institutional quality and income: Empirical evidence for sub-Saharan Africa - Huy Quang Doan (Economies, 2019)
This paper looks at how trade liberalization and institutional quality influence real income. Previous evidence has provided mixed results, and we find that indicators representing trade liberalization have been very weak. By using strongly balanced panel data of 45 Sub-Saharan African countries covering the last 34 years (1980-2013), along with numerous advanced econometric instruments (random effect, fixed effect, system-generalized method of moments, pooled mean group) and composite trade indicators (KOF indicators), this paper determines the impact of trade liberalization, social factors and political globalization on real income per capita in both static and dynamic settings. The paper also considers short-term and long-term effects. The study confirms that free trade has a significant positive impact on the growth of real income per capita in static and dynamic settings. However, it also finds that countries must pay in the short-term to gain more significantly in the long-term. Further, we point out that social factors, especially information flows, can have significant but varying influences on real income under different scenarios and that political globalization both challenges and gives opportunities for improving living standards. We also find that institutional quality is a key factor for economic development in any situation.
Keywords: F6; O43; O47; 330; trade liberalization; globalization; institutional quality; economic growth